Religious Fundamentalism: Threats to the Life of the Nation and Religion in Indonesia - Endrizal; Suharti (Tsaqofah, 2023)
This study discusses religious fundamentalism movements that can threaten the life of the nation and State. This research is located in West Sumatra, North Sumatra, and Riau. This research is qualitative. This study collected data using observation, in-depth interviews, and literature studies. Data is analyzed by reducing, displaying, analyzing, processing, making conclusions, and verifying data. The results of this study indicate that the emergence of religious fundamentalism is caused by understanding textually the verses, rejecting Western modernism, and political power is disadvantaged. The proposal from this research in counteracting religious fundamentalism is using deradicalization of the State, optimizing the role of religious leaders, and deradicalization of educational institutions. This research still needs to be continued by other researchers related to deradicalization and moderation in religion.